Sevoflurane as bridge therapy for plasma exchange and Anakinra in febrile infection–related epilepsy syndrome - Manuela L’Erario (Wiley, 2021)
Abstract Febrile infection–related epilepsy syndrome (FIRES) is a devastating immune inflammatory–mediated epileptic encephalopathy. Herein, we discuss a previously healthy 8‐year‐old boy with FIRES in whom high dosages of conventional and nonconventional anesthetics were ineffective in treating SE, as were ketogenic diet, intravenous corticosteroids, and immunoglobulins. After 29 days of prolonged SRSE, the patient was successfully treated with sevoflurane paired with plasma exchange, for a total of five days, thus obtaining a stable EEG suppression burst pattern with no adverse events. Anakinra at the dosage of 100 mg b.i.d. was started seven days after sevoflurane and plasma exchange had been discontinued and was effective in ensuring non‐recurrence of SE. Sevoflurane as bridge therapy for immunosuppressive treatment could be considered an early, safe, and effective option in treating convulsive SE in which an autoimmune‐inflammatory etiology can reasonably be hypothesized.